Assesment Of Geography For 21st Century - suhendro suhendro; Dede Sugandi; Mamat Ruhimat (Jurnal Georafflesia: Artikel Ilmiah Pendidikan Geografi, 2020)
Assessment or assessment is a general term covering all the methods commonly used to assess the performance of individual students or groups. The assessment process includes gathering evidence to demonstrate student learning achievement. In essence, the basis of self-assessment must be conditioned to the age so that students can compensate for the demands due to the changing times. 21st Century Assessment is a form of implementation of the development of the times, to achieve the achievement of the implementation of the 21st century assessment, so many assessment bases are conditioned to equalize the ability due to changing times. Assemen on subjects have been implemented by several related parties, one of the subjects which has bases of assessment in the equalization of the changing times associated with 21st century assessment is the subject of Geography. As for this study using the literature study method, the data used is related to the assessment of geography subjects, the data sources used are from Google Scholar, ERIC, Sage Journal, and Taylor and Francis Group Jounal. The results of this article are in the form of geo-based assessment (HOTS) Higher Order Thinking Skills, TIGAS-based geography assessment (Trends in International Geography Assessment Study), and 21st Century assessment framework for Geography.